2017
DOI: 10.1038/s41598-017-04493-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Global DNA Methylation and Telomere Length in Healthy Adolescents

Abstract: Emerging evidence suggests that epigenetics regulates telomere dynamics in adults. However, the relationship between these pathways in children and youth remains unknown. Thus, we examined this association in 542 healthy adolescents aged 14 to 18 years old (44.8% African Americans; 55.2% females). Global DNA methylation level (%5-mC) was quantified using ELISA method. Leukocyte telomere length (LTL) was defined as relative telomere to single copy gene (T/S) ratio. Multiple linear regression models, adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
(40 reference statements)
0
29
0
1
Order By: Relevance
“…TL has been found to be associated with epigenetic alterations across different populations and environmental exposures [22][23][24]. TL was not only associated with the global methylations among young adults [23], but also associated with specific DNA methylation changes in response to gestational age among placental samples and in response to smoking exposure among older adults [22,24], respectively. Given that, we hypothesized that TL might be associated with the MS and hence the MS might be able to reflect the aging process which the TL is involved in.…”
Section: Introductionmentioning
confidence: 94%
“…TL has been found to be associated with epigenetic alterations across different populations and environmental exposures [22][23][24]. TL was not only associated with the global methylations among young adults [23], but also associated with specific DNA methylation changes in response to gestational age among placental samples and in response to smoking exposure among older adults [22,24], respectively. Given that, we hypothesized that TL might be associated with the MS and hence the MS might be able to reflect the aging process which the TL is involved in.…”
Section: Introductionmentioning
confidence: 94%
“…In this review, we describe a new hypothesized factor in this intergenerational transmission process: epigenetics – molecular processes that change the expression of genes independent of changing DNA sequence. Epigenetic marks have been observed in genes thought to impact stress response (Edelman et al., ; de Rooij et al., ), emotion regulation (Puglia, Lillard, Morris, & Connelly, ), disease susceptibility (Dong, Huang, Gutin, Dong, & Zhu, ), and mental disorders (Dammann et al., ; Melas et al., ; Na et al., ; Wang, Feng, et al., ); all factors that can lead to compromised life courses. While more research is needed to clarify the role of epigenetics in phenotypic expression in these areas, epigenetic intergenerational transmission could potentially be a biological component of the reproduction of poverty across generations…”
Section: Introductionmentioning
confidence: 99%
“…Although the sample size was limited, this exploratory study suggests global DNA hypomethylation may be related to decreased TL in peripheral blood leukocytes. A recent larger study using an ELISA-based method to determine global 5mC content also showed that decreased global DNA methylation was associated with shortened TL in adolescents [71]. Taken together these studies provide the impetus for future studies, involving larger cohorts, to focus on gene-specific DNA methylation signatures potentially related to TL.…”
Section: Epigenetic Regulation Of Telomere Lengthmentioning
confidence: 71%